Market-internal financial regulation in sports as an anticompetitive institution - Oliver Budzinski (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2017)
Financial regulation in sports is usually discussed in the context of representing an instrument against "financial doping". Notwithstanding the merits of this discussion, this paper takes the opposite perspective and analyses how market-internal financial regulation itself may anticompetitively influence sporting results. Virtually every regulative financial intervention distorts sporting competition to some extent and creates beneficiaries and losers. Sometimes, the actual winners and losers of financial regulation stand in line with the (legitimate) goals of the regulation like limiting financial imbalances or preventing distortive midseason insolvencies of teams. However, financial regulation may also display unintended side-effects like protecting hitherto successful teams from new challengers, cementing the competitive order, creating foreclosure and entry barriers, or serving vested interests of powerful parties. All of these effects may also be hidden agendas by those who are implementing and enforcing market-internal financial regulation or influencing it. This paper analyses various types of budget caps (including salary caps) with respect to potentially anticompetitive effects. UEFA's so-called Financial Fair Play Regulations are highlighted as an example. Furthermore, the paper discusses allocation schemes of common revenues (like from the collective sale of broadcasting rights) as another area of financial regulation with potentially anticompetitive effects. Eventually, the effects of standards for accounting, financial management, and auditing are discussed.
Keywords: Z20; Z23; L40; L83; K21; 330; sports economics; financial regulation; budget caps; salary caps; financial fair play; financial doping; collective sale of media rights; sports broadcasting rights; revenue sharing